2022
DOI: 10.1038/s42003-022-03637-w
|View full text |Cite
|
Sign up to set email alerts
|

PI3Kδ activity controls plasticity and discriminates between EMT and stemness based on distinct TGFβ signaling

Abstract: The stem cells involved in formation of the complex human body are epithelial cells that undergo apicobasal polarization and form a hollow lumen. Epithelial plasticity manifests as epithelial to mesenchymal transition (EMT), a process by which epithelial cells switch their polarity and epithelial features to adopt a mesenchymal phenotype. The connection between the EMT program and acquisition of stemness is now supported by a substantial number of reports, although what discriminates these two processes remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 62 publications
5
8
0
Order By: Relevance
“…TGFβ overexpression leads to CCA tumorigenesis and metastasis 41 . Furthermore our recent work demonstrated that PI3Kδ activity discriminates EMT and stemness based on distinct TGFβ signalling in malignant hepatocytes 30 . Interestingly in this study our results showed that PI3Kδ expression in CCA cells increased TGFβ expression both in vitro 3D cultures and in vivo.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…TGFβ overexpression leads to CCA tumorigenesis and metastasis 41 . Furthermore our recent work demonstrated that PI3Kδ activity discriminates EMT and stemness based on distinct TGFβ signalling in malignant hepatocytes 30 . Interestingly in this study our results showed that PI3Kδ expression in CCA cells increased TGFβ expression both in vitro 3D cultures and in vivo.…”
Section: Discussionsupporting
confidence: 55%
“…41 Furthermore our recent work demonstrated that PI3Kδ activity discriminates EMT and stemness based on distinct TGFβ signalling in malignant hepatocytes. 30 Interestingly in this study our results showed that PI3Kδ expression in CCA cells increased TGFβ expression both in vitro 3D cultures and in vivo. Particularly PI3Kδ expression in CCA cells promoted secretion of TGFβ and angiogenic factors such as VEGF and bFGF in the serum of xenograft mice (Figure 5).…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…TGF-β regulates MIR100HG transcription and thus the release of its hosted miRs, inducing EMT, encouraging cell motility and metastasis 25 . Here, we identi ed many TGF-β related genes such as FGF1 76 , KDM6B 77 , LIF 78 , PIK3CD 79 , PXDC1 and TAGLN 80 were signi cantly downregulated in the two CRISPRi groups compared to the control (Extended Data Fig. 9).…”
Section: Cre Cluster Harbouring Ncms Located At the Mir100hg Locus Re...mentioning
confidence: 94%
“…And in 2015, the adult liver organoid model capable of long-term stable expansion in vitro was established. The need for disease research has led to the development of organoid models of liver cancer to study the initiation and progression of liver cancer with progressive applications in cancer development mechanisms (11)(12)(13)(14)(15)(16), preclinical research (17), personalized medicine (18)(19)(20)(21) and drug screening (22,23). Many factors can induce the oncogenesis of the liver cancer, organoid can also be help to study the mechanism of oncogenesis and development of HCC.…”
mentioning
confidence: 99%